2018
DOI: 10.18632/oncotarget.24952
|View full text |Cite
|
Sign up to set email alerts
|

Over-activation of AKT signaling leading to 5-Fluorouracil resistance in SNU-C5/5-FU cells

Abstract: Here, we investigated whether over-activation of AKT pathway is important in the resistance to 5-fluorouracil (5-FU) in SNU-C5/5-FU cells, 5-FU-resistant human colon cancer cells. When compared to wild type SNU-C5 cells (WT), SNU-C5/5-FU cells showed over-activation of PI3K/AKT pathway, like increased phosphorylation of AKT, mTOR, and GSK-3β, nuclear localization of β-catenin, and decreased E-cadherin. Moreover, E-cadherin level was down-regulated in recurrent colon cancer tissues compared to primary colon can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 52 publications
7
20
0
Order By: Relevance
“…To our best knowledge, the regulation of AMPK and PI3K/AKT pathways are complicated. On the basis of several previous researches [35,36], we speculated that miR-622 affected AMPK and PI3K/AKT pathways might through adjusting the up-stream interrelated genes expression of these two pathways. Further researches are still necessary to probe this issue.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To our best knowledge, the regulation of AMPK and PI3K/AKT pathways are complicated. On the basis of several previous researches [35,36], we speculated that miR-622 affected AMPK and PI3K/AKT pathways might through adjusting the up-stream interrelated genes expression of these two pathways. Further researches are still necessary to probe this issue.…”
Section: Discussionmentioning
confidence: 97%
“…AMPK and PI3K/AKT pathways are proved to be activated in colon cancer [32,33]. It is reported that unusual activations of AMPK and PI3K/AKT pathways contribute to growth, metastasis and drug resistance of colon cancer [34][35][36]. Hereon, silencing UNC5B-AS1 hampered AMPK and PI3K/AKT pathways in HCT116 and Caco-2 cells.…”
Section: Discussionmentioning
confidence: 98%
“…The PI3K/AKT pathway is associated with MDR in various cancer cells, such as doxorubicinresistant breast cancer and fluorouracil-resistant colon cancer cells [23,24]. SIRT1 promotes membrane localization and activation of AKT [25].…”
Section: Activation Of Akt Correlates With Sirt1 Upregulation In Drugmentioning
confidence: 99%
“…Phospholipase A2 activation results in the release of arachidonic acid, which is the substrate of COX-2, and as a consequence of this activity PGE2 is produced [ 33 ]. This last eicosanoid stimulates proliferation of cells through the Wnt/ β -catenin signalling pathways [ 33 ] and inhibits apoptosis by stabilization of survivin-procaspase 3 complexes [ 34 ]. The effect of IRS-4 on procaspase 3 levels in RKO cells was dependent on PI3K because it was inhibited by wortmannin incubation.…”
Section: Discussionmentioning
confidence: 99%